1997
DOI: 10.3168/jds.s0022-0302(97)76149-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Live Yeast Culture and Enzymes on In Vitro Ruminal Fermentation and Milk Production of Dairy Cows

Abstract: Live yeast culture (Saccharomyces cerevisiae) grew best on malt extract agar and required incubation under aerobic conditions to maximize the number of viable cells. In sterile, anaerobic ruminal fluid that had been supplemented with malt extract, yeast cells remained viable and metabolically active for up to 48 h, as indicated by the production of ethanol. A supplement containing live yeast and enzymes was fed twice daily with a diet of 50:50 (wt/wt) forage to concentrate (dry matter basis) to continuous ferm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 16 publications
6
51
0
3
Order By: Relevance
“…It has also been suggested that yeasts utilize nutrients, such as lactic acid, which if allowed to accumulate in the rumen, could suppress bacterial growth and/or suppress DM intake by lowering rumen pH (Nisbet and Martin, 1990). A more recently suggested possibility is that growth of yeast in the rumen utilizes trace amounts of dissolved oxygen, particularly at the interface of the cellulolytic bacteria and fiber, thereby stimulating growth of rumen bacteria to which oxygen is toxic (Newbold et al, 1996). It seems clear that for these mechanisms to be functional, yeasts in the YP would have to be viable, in the sense of being able to grow, for at least a short period of time in the rumen.…”
Section: Article In Press G Modelmentioning
confidence: 99%
“…It has also been suggested that yeasts utilize nutrients, such as lactic acid, which if allowed to accumulate in the rumen, could suppress bacterial growth and/or suppress DM intake by lowering rumen pH (Nisbet and Martin, 1990). A more recently suggested possibility is that growth of yeast in the rumen utilizes trace amounts of dissolved oxygen, particularly at the interface of the cellulolytic bacteria and fiber, thereby stimulating growth of rumen bacteria to which oxygen is toxic (Newbold et al, 1996). It seems clear that for these mechanisms to be functional, yeasts in the YP would have to be viable, in the sense of being able to grow, for at least a short period of time in the rumen.…”
Section: Article In Press G Modelmentioning
confidence: 99%
“…In this study, a dried live S. cerevisae culture was supplied, and its daily supply in ad libitum feeding system provided a continued flow of yeast, as S. cerevisiae is viable only for only 24 to 30 h in the rumen (Kung et al, 1997;Durand-Chaucheyras et al, 1998). In agreement with previous studies (Vyas et al 2014a, b), ADFI of heifers was unaffected by S. cerevisae.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, yeasts have no replication capacity in the rumen and remain active for a maximum period of 48 h (Kung et al, 1997). Therefore, a continuous yeast administration is required to achieve their beneficial effects on ruminal fermentation.…”
Section: Rumenmentioning
confidence: 99%
“…Ethanol is produced by certain species of rumen bacteria (Ruminococcus albus; Czerkawski, 1986) or fungi such as Saccharomyces cerevisiae (Kung et al, 1997), Orpinomyces joyonii (Kovar et al, 2000) and Pyromyces communis (Julliand et al, 1998) during their carbohydrate metabolism. The amount of ethanol formed in this way is variable and greatly depends on the composition of microflora and carbohydrate content of the ration.…”
Section: Acta Veterinaria Hungarica 51 2003mentioning
confidence: 99%